“Eu participo porque...” reflexões sobre a participação do cidadão comum nos telejornais de Imperatriz (MA) - BARBOSA, Kellen Ayana Alves Ceretta (2022)
This dissertation analyzes the participation of citizens in the television news of Imperatriz (MA) and has as objective to understand what is the intention of the common citizen to collaborate with the construction of the news by sending content produced by himself and that he thinks is important to be transmitted. Among the contents sent are: videos, photos and/or agenda suggestions. These individuals have assumed the role of co-producer of the news and act as if they were. The research also aims to understand why these people help the TV journalist in the production of the news, even though they are not mentioned and even less receive financial incentive. With an interactionist approach, the empirical development of the work presents a quali- quantitative methodology. As the work is based on symbolic interactionism (BLUMER, 1980); (WEXLER, 1983), we understand that it is of fundamental importance to carry out an in-depth study on qualitative issues, which are based on the individual's social interaction. As a method, it was necessary to use the Survey collection technique, with the being able to 'find' this participatory public and carry out the mapping (BUENO, 2012); (BIEMBENGUT, 2008) of these individuals. And as an interactionist technique, we made use of semi-structured interviews with 10 citizens who participate, or have participated, with the city's television news. It is important to emphasize that this research is based on the relationship of the common citizen who participates with the newsrooms of television news, from the point of view of these individuals and not of the journalist. Among the main results, we found that the vast majority participate with television news programs since they believe in the 'power' they have to help the population in solving community problems.